Enhancing the Clinical Potential of AAV Vectors by Capsid Engineering to Evade Pre-Existing Immunity - Bartel, Melissa; Schaffer, David; Büning, Hildegard (Frontiers in Microbiology, 2011)
Vectors based on adeno-associated viruses have shown considerable promise in both preclinical models and increasingly in clinical trials. However, one formidable challenge is pre-existing immunity due to widespread exposure to numerous AAV variants and serotypes within the human population, which affect efficacy of clinical trials due to the accompanying high levels of anti-capsid neutralizing antibodies. Transient immunosuppression has promise in mitigating cellular and humoral responses induced by vector application in naïve hosts, but cannot overcome the problem that pre-existing neutralizing antibodies pose towards the goal of safe and efficient gene delivery. Shielding of AAV from antibodies, however, may be possible by covalent attachment of polymers to the viral capsid or by encapsulation of vectors inside biomaterials. In addition, there has been considerable progress in using rational mutagenesis, combinatorial libraries, and directed evolution approaches to engineer capsid variants that are not recognized by anti-AAV antibodies generally present in the human population. While additional progress must be made, such strategies, alone or in combination with immunosuppression to avoid de novo induction of antibodies, have strong potential to significantly enhance the clinical efficacy of AAV vectors.